Blockchain Based Smart Contract Usability in Agreement on Building Works : Finnish Regulatory Framework - Hellgrén, Juulia (My University, 2022)
The construction industry is known for its weak development of productivity and digitalization. In addition, complex structure of agreement on building works, multistaged contracting practices and prevalence of disputes provide a fertile context for the research. This thesis provides an overview to agreement on building works and their regulatory framework in Finland. Purpose, general content and contracting process is examined to understand related challenges and potential areas for improvement. Blockchain based smart contracts are studied as a potential technology to be utilized in construction agreements. Features, operational logic, benefits, and legal position of smart contracts are addressed. Blockchain and smart contract technologies modify the way contracts are formed and understood. Possibilities and benefits in different sections and applications are not clear to the extent enabled by the technology. Therefore, this thesis contributes to research concerning opportunities smart contracts could offer in different industries, operations and activities. Carried out as literature research, this study examines how smart contract technology could be utilized in agreements on building work and what kind of challenges are related to implementation of the technology in the Finnish legal environment. On the basis of literature review of agreement on building works, blockchain and smart contract technologies, a case study is built in the study. Use case example assesses suitability and usability of smart contracts in agreement on building works. Based on the study, Finnish legislation does not appear to pose direct obstacles to the creation of a legally valid agreement binding on contracting parties. The assessment of the mechanisms and binding nature of the agreement is in principle no different from the traditional agreement process. However, the study identified challenges that slow down or may hamper the willingness to adopt the technology and practical pilots. The challenges relate to technical requirements, investments in terms of time and money, ambiguity in the functioning of technology and unclarities concerning applicable legislation, legal interpretation and legal status of smart contracts. It can be concluded from the research results that smart contract technology is not yet mature enough or does not have sufficient user experience for experimenting the technology in the construction industry. However, in the light of the potential benefits and in the framework of enabling legislation so far, it would be possible to explore and test practical use cases in order to increase digitization, efficiency and trust in agreements on building works.

Rakennusala tunnetaan heikosta tuottavuuden kehityksestä ja hitaasta digitalisaatiosta. Tässä pro gradu -tutkielmassa tutkitaan urakkasopimuksia sekä niiden lainsäädännöllistä viitekehystä Suomessa. Monimutkainen urakkasopimusrakenne, monivaiheinen sopimusprosessi ja erimielisyyksien yleisyys tarjoavat hedelmällisen kontekstin tutkimukselle. Urakkasopimusten merkitystä, yleistä sisältöä ja sopimisprosessia tutkitaan sopimukseen liittyvien haasteiden ja kehitysmahdollisuuksien ymmärtämiseksi. Lohkoketjuteknologiaan perustuvia älysopimuksia tutkitaan mahdollisena, urakkasopimuksessa hyödynnettävänä teknologiana. Älysopimusten ominaisuuksia, toimintaperiaatetta, hyötyjä ja lainsäädännöllistä asemaa tarkastellaan tutkimuksessa. Lohkoketju- ja älysopimusteknologiat muokkaavat niitä tapoja, joilla sopimukset muodostetaan ja ymmärretään. Teknologian tarjoamia mahdollisuuksia eri aloilla sekä potentiaalisia hyötyjä ei ymmärretä täydessä laajuudessa. Tämä tutkielma laadittiin osaltaan täydentämään älysopimusten mahdollisuuksien tutkimusta eri aloilla, toiminnoissa ja toimenpiteissä. Kirjallisuustutkimuksen menetelmin tutkitaan kuinka älysopimusteknologiaa voitaisiin hyödyntää urakkasopimuksissa ja millaisia haasteita teknologian käyttöön liittyy Suomen lainsäädännön viitekehyksessä. Urakkasopimusten ja lohkoketjuteknologian sekä älysopimusten kirjallisuuskatsauksen pohjalta tutkimuksessa rakennetaan käyttötapausesimerkki, jossa arvioidaan teknologian soveltuvuutta ja käytettävyyttä urakkasopimuksessa ja sen osissa. Tutkimuksen perusteella vaikuttaa siltä, että Suomen lainsäädäntö ei aseta suoranaisia esteitä laillisesti pätevän ja osapuolia sitovan sopimuksen synnylle. Sopimuksen syntymekanismien ja sitovuuden arviointi ei lähtökohtaisesti eroa perinteisestä sopimisprosessista. Tutkimuksessa havaittiin kuitenkin haasteita, jotka hidastavat tai voivat haitata teknologian käyttöönottohalukkuutta ja käytännön pilottihankkeita. Haasteet liittyvät teknisiin vaatimuksiin, investointeihin, teknologian toimivuuden sekä älysopimusten lainsäädännön ja laillisen aseman epäselvyyksiin. Tutkimustuloksista voidaan päätellä, että älysopimusteknologia ei ole vielä riittävän kypsä tai siitä ei ole riittävästi käyttökokemusta ja näyttöä, jotta teknologiaa uskallettaisiin lähteä kokeilemaan myös rakennusalalla ja urakkasopimuksissa. Potentiaalisten hyötyjen valossa ja toistaiseksi mahdollistavan lainsäädännön puitteissa konkreettisten käyttötapausten tutkiminen ja kokeileminen olisi kuitenkin mahdollista digitalisaation, tehokkuuden ja luottamuksen lisäämiseksi urakkasopimuksissa.
Keywords: agreements; blockchains; construction; contract law; fi=Talousoikeus|en=Business Law|; fi=Talousoikeuden maisteriohjelma|en=Master's Programme in Business Law|